Estonian youths´ attitudes and perceptions towards the Olympic brand and its relation with Olympic Education - Kaibald, Liis (Πανεπιστήμιο Πελοποννήσου, 2013)
This study investigates Estonian youth´s attitudes and perceptions towards the Olympic brand and its relation with Olympic Education. Both, qualitative and quantitative studies were used to gather and analyze data. Stratified random sampling was used for both qualitative and quantitative research. The aimed population was youth from different parts of Estonia: north, south, east and west, where at some of the youth have been going through Olympic Education project and some have not. Study 1 consisted of a qualitative research with semi-structure interviews completed with 11 young participants aged 12 to 19 years. Study 2 consisted of a quantitative research with a questionnaire carried out on 397 adolescentsalso aged 12 to 19 years. Also, interviewees are asked questions to better understand their knowledge towards the Olympic Movement. Finings of this study indicate that 1) Estonian youth gain most of their knowledge and understanding of the Olympic Games through informal pedagogical sites, whereas youths´ knowledge and understanding of the Olympics is not in specific connection with Olympism or the Olympic ideals, but they are familiar with general human values and the Olympic Games; 2) Estonian youth place higher meaning to the Olympic brand as the attributes that they strongly associated and found most important reflect rather the Olympic values and fundamental principles of Olympism than characteristics of major sport event; 3) Olympic Education project “School Olympic Games” does not clearly affect youths´ neither attitudes nor perceptions regarding the Olympic brand.
Keywords: Φυσική αγωγή και εκπαίδευση - Εσθονία; Ολυμπιακοί αγώνες - Φιλοσοφία; Ολυμπιακοί αγώνες - Ευγενής ανταγωνισμός; Physical education and training - Estonia; Olympics - Philosophy; Olympics - Fair play; Olympic brand; Υoung brand consumers; Olympic Education; Υoung people and Olympic brand; Ολυμπιακό σήμα; Νέοι καταναλωτές επώνυμου προϊόντος; Ολυμπιακή Εκπαίδευση; Νέοι και Ολυμπιακό σήμα